2015
DOI: 10.1136/gutjnl-2014-308153
|View full text |Cite
|
Sign up to set email alerts
|

The composition and differentiation potential of the duodenal intraepithelial innate lymphocyte compartment is altered in coeliac disease

Abstract: Thus, we demonstrate previously unappreciated diversity and plasticity of the innate IEL compartment and its loss of differentiation potential in patients with RCDII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…3f) matched previously described21 biological annotations (Fig. 5, black annotations)including the CRTH2 + ILC2 (cluster 16), c-KIT + ILC3 (cluster 5) and CD56 -CD127lineage -IELs (cluster 19, 13, 18, 14, 6 and 8), the latter representing innate type of lymphocytes with dual T cell precursor and NK/ILC traits[23][24][25] .…”
supporting
confidence: 74%
“…3f) matched previously described21 biological annotations (Fig. 5, black annotations)including the CRTH2 + ILC2 (cluster 16), c-KIT + ILC3 (cluster 5) and CD56 -CD127lineage -IELs (cluster 19, 13, 18, 14, 6 and 8), the latter representing innate type of lymphocytes with dual T cell precursor and NK/ILC traits[23][24][25] .…”
supporting
confidence: 74%
“…It has been shown that IELs, specifically cytotoxic T cell receptor (TCR)‐αβ + T cells, which undergo natural killer (NK)‐like reprogramming on interacting with epithelial stress‐induced ligands, and IL‐15, up‐regulated upon exposure to toxic gliadin peptides, promote epithelial destruction . Contributions of other types of lymphoid cells to the innate immune response in CD are suspected, but these are currently unclear . Recent studies have implicated ILCs in the pathogenesis of a variety of intestinal inflammatory disorders ; however, data regarding the repertoire of human proximal small intestinal (SI) ILCs and their alterations in CD are limited .…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal cell phenotype includes the loss of surface CD3 with preservation of cytoplasmic CD3ε [39,40] and rearranged TCRγ chains [38,41]. These abnormal and highly proliferative IEL are suggested to give rise to T-cell lymphoma [42], while others suggest innate IEL giving rise to enteropathy-associated T-cell lymphoma (EATL) [26,43]. However, lymphoma in celiac disease patients is not confined to the EATL [44].…”
Section: Celiac Diseasementioning
confidence: 99%
“…These IEL are CD8 + T cells carrying the αβ T-cell receptor (TCR) or CD4 - CD8 - γδTCR + T cells [24]. Innate IEL are drastically reduced upon intestinal inflammation in celiac disease [25,26]. Both αβ + and γδ + IEL express NKG2D [27], a receptor recognizing self-proteins induced by stress, infection and transformation [28], while the inhibitory NKG2A receptors are downregulated [29].…”
Section: Celiac Diseasementioning
confidence: 99%